2011
DOI: 10.1371/journal.pone.0017269
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Extra-Nigral Damage Predicts Behavioural Deficits in a Rat Proteasome Inhibitor Model of Parkinson's Disease

Abstract: Establishing the neurological basis of behavioural dysfunction is key to provide a better understanding of Parkinson's disease (PD) and facilitate development of effective novel therapies. For this, the relationships between longitudinal structural brain changes associated with motor behaviour were determined in a rat model of PD and validated by post-mortem immunohistochemistry. Rats bearing a nigrostriatal lesion induced by infusion of the proteasome inhibitor lactacystin into the left-medial forebrain bundl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
68
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(75 citation statements)
references
References 87 publications
(128 reference statements)
6
68
1
Order By: Relevance
“…It is thought that neurodegeneration arises from the formation of toxic misfolded oligomers of a-synuclein that may exert their toxic effects by disrupting cell membranes such as those of the mitochondria. a-Synuclein proteostasis depends on both the ubiquitin-proteasome and lysosomal pathways of protein turnover, so disruption of either of these pathways by, e.g., proteasome inhibitors and lysosomal storage diseases, might be expected to lead to increased accumulation of a-synuclein and eventually to the formation of a-synuclein aggregates (Lopez and Sidransky 2010;Vernon et al 2011). The role of the large Lewy body aggregates is controversial.…”
Section: A-synuclein Variantsmentioning
confidence: 99%
“…It is thought that neurodegeneration arises from the formation of toxic misfolded oligomers of a-synuclein that may exert their toxic effects by disrupting cell membranes such as those of the mitochondria. a-Synuclein proteostasis depends on both the ubiquitin-proteasome and lysosomal pathways of protein turnover, so disruption of either of these pathways by, e.g., proteasome inhibitors and lysosomal storage diseases, might be expected to lead to increased accumulation of a-synuclein and eventually to the formation of a-synuclein aggregates (Lopez and Sidransky 2010;Vernon et al 2011). The role of the large Lewy body aggregates is controversial.…”
Section: A-synuclein Variantsmentioning
confidence: 99%
“…While some in vitro studies demonstrated particular sensitivity of DA neurons to the action of these compounds [11,26,27], other reports showed only slight differences between vulnerability of DA and ␥-aminobutyric acid (GABA) neurons [12], or even a greater resistance of DA neurons compared to non-DA ones [28]. In turn, there is a clear evidence from magnetic resonance imaging studies that the administration of lactacystin into the rat SN pars compacta (SNc) or medial forebrain bundle (MFB) results in widespread extra-nigral volume changes [18,19,24]. Qualitative assessment confirmed that lactacystin, besides the death of DA neurons in the SNc, produced additional neuronal loss in the SN pars reticulata (SNr), ventral tegmental area (VTA), thalamus and certain extranigral nuclei in proximity to the injection tract [18,19].…”
Section: Introduction Q3mentioning
confidence: 99%
“…Neuronal degeneration was accompanied by a sharp decrease in the striatal DA content and impairment of the motor dysfunction, reversed by l-DOPA treatment [21]. Furthermore, lactacystin treatment led to the formation of cytoplasmic ␣-synuclein-and ubiquitinimmunopositive inclusion in the SN [18,19,[22][23][24][25]. Thus, the advantage of the lactacystin model over the conventional 6-OHDA model is that, besides the loss of DA neurons in the SN, it represents the cardinal feature of PD, namely abnormal protein degradation.…”
Section: Introduction Q3mentioning
confidence: 99%
See 2 more Smart Citations